A 5deg x 5deg deep H i survey of the M81 group. Issue 1 (11th March 2019) - Sorgho, A; Foster, T; Carignan, C; Chemin, L
ABSTRACT: A $25\, \rm deg^2$ region, including the M81 complex (M81, M82, and NGC 3077), NGC 2976, and IC2574, was mapped during ∼3000 h with the DRAO synthesis telescope. With a physical resolution of ∼1 kpc, these observations allow us to probe a large region down to column density levels of ${\sim }1× 10^{18}\, \rm cm^{-2}$ over 16 km s −1, mapping the extent of the H i arm connecting the system and NGC 2976, and resolving the H i clouds adjacent to the arm. The observations also reveal a few clouds located between the system and IC 2574, probably tidally stripped from a past interaction between the two systems. Given the regular velocity distribution in the H i envelope of the system, we attempt and derive an idealized large-scale rotation curve of the system. We observe a flat trend for the rotation velocity of the overall system from 20 kpc out to 80 kpc, well beyond the outskirts of the M81 disk, although with asymmetries like a wiggle at the vicinity of M82. This supports the assumption that intergalactic gas and galaxies in the system participate to a large-scale ordered rotation motion which is dominated by M81. Also, our H i analysis of the group further supports the hypothesis that the galaxies forming the system moved closer from afar, in agreement with numerical simulations.